Life Cycle and Development of Diptera 2020
DOI: 10.5772/intechopen.88854
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Shifts inPhilornisLarval Behaviour and Rapid Changes inPhilornis downsiDodge & Aitken (Diptera: Muscidae): An Invasive Avian Parasite on the Galápagos Islands

Abstract: The parasitic larvae of Philornis downsi Dodge & Aitken (Diptera: Muscidae) were first discovered in Darwin's finch nests on the Galápagos Islands in 1997. Larvae of P. downsi consume the blood and tissue of developing birds, causing high in-nest mortality in their Galápagos hosts. The fly has been spreading across the archipelago and is considered the biggest threat to the survival of Galápagos land birds. Here, we review (1) Philornis systematics and taxonomy, (2) discuss shifts in feeding habits across Phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Additionally, up to three confirmed female flies (with ovipositors extended) were seen in a nest at one time, which is consistent with previous population genetic studies indicating that multiple P. downsi females oviposit per nest (Dudaniec et al 2010), and provides new evidence that oviposition events by several flies can take place simultaneously. Evidence of female flies in the nest cavity during the incubation phase supports prior reports of P. downsi oviposition during the incubation phase in nests of Darwin's finches (Cimadom et al 2016;Common et al 2019;Cimadom and Tebbich 2020). On the other hand, observations of fly visitation and oviposition-like behavior during the late nestling phase concur with findings of first instar P. downsi larvae in host nests with nestlings close to fledging age (C. Pike, unpublished data; Kleindorfer et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, up to three confirmed female flies (with ovipositors extended) were seen in a nest at one time, which is consistent with previous population genetic studies indicating that multiple P. downsi females oviposit per nest (Dudaniec et al 2010), and provides new evidence that oviposition events by several flies can take place simultaneously. Evidence of female flies in the nest cavity during the incubation phase supports prior reports of P. downsi oviposition during the incubation phase in nests of Darwin's finches (Cimadom et al 2016;Common et al 2019;Cimadom and Tebbich 2020). On the other hand, observations of fly visitation and oviposition-like behavior during the late nestling phase concur with findings of first instar P. downsi larvae in host nests with nestlings close to fledging age (C. Pike, unpublished data; Kleindorfer et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Previously, P. downsi larvae were only present in Darwin's finch nests once the host nestlings had hatched (Fessl & Tebbich, 2002;O'Connor et al, 2014). However, in recent years, there have been a growing number of observations of P. downsi larvae in nests during the incubation phase suggesting that larvae are feeding on incubating females (Cimadom et al, 2016;Common et al, 2019). Incubating female finches have been found to express P. downsi-specific antibodies (Huber et al, 2010), and females with higher antibody levels were found to have fewer parasites in their nest (Knutie et al, 2016;Koop, Owen, Knutie, Aguilar, & Clayton, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The adult fly has been present in the Galápagos since at least 1964 (Causton et al, 2006), but its larvae were first reported in Darwin's finch nests on Santa Cruz Island in 1997 (Fessl, Couri, & Tebbich, 2001) despite long-term field study into Darwin's finches on other islands since 1973 (Grant & Grant, 2002). Field research found P. downsi requires c. 4-7 days to develop through three instar stages and reach pupation (Common, Dudaniec, Colombelli-Négrel, & Kleindorfer, 2019;Kleindorfer, Peters, et al, 2014). In this newly evolving host-parasite system, mortality has been high in both P. downsi and its Darwin's finch hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during 2000 to 2004 on Santa Cruz Island, P. downsi were only found in Darwin's finch nests with chicks (100% prevalence), but, since 2012 on Santa Cruz Island, P. downsi have regularly been found in Darwin's finch nests with eggs (80% prevalence in some species and some years) and in most nests with chicks (83% to 100% prevalence) [ 35 ], indicating adult P. downsi are ovipositing earlier in the nesting cycle. By contrast, on Floreana Island, during 2004 to 2016, P. downsi larvae and pupae were uncommon in nests with eggs (2% prevalence) but were found in all highland nests with chicks (100% prevalence) [ 36 ].…”
Section: Introductionmentioning
confidence: 99%